Evaluación de rendimiento de 4 variedades de rábano (raphanus sativus l.) en el cantón arenillas - Gomez Montesdeoca, Favio Enrique (Machala : Universidad Técnica de Machala, 2021)
In Ecuador there are approximately 14455 hectares cultivated of radish, the main producing provinces are in the north of the country such as Imbabura, Tungurahua, Cotopaxi and Chimborazo. Radish is a food consisting of a large amount of water as the main element, as well as carbohydrates and fiber, so it provides low levels of calories, being recommended by nutritionists in weight-regulating diets, it contains an important amount of vitamins, of those that stand out those of group C and folates. Those of group C have antioxidant action, they intervene in the prevention of diseases such as cardiovascular or degenerative diseases and favor the formation of collagen, teeth, bones or red blood cells. The test area is located at the following geographic coordinates: longitude 80 ° 06'48.51 ”W; latitude 3 ° 45'27.67 ”S, and a height of 197 meters above sea level. It was held at the La Florida site of the Palmales Parish of the Cantón Arenillas. The area corresponds to the dry to semi-humid tropical mega-thermal climate whose main characteristics correspond to an annual rainfall total between 1000 and 1500 mm, collected from December to May, the dry season is very marked, it extends from June to November; and the average elevated temperatures are higher than 24 ° C according to the soil taxonomy map of the Atlas of the El Oro Province. The taxonomic classification of the soil, silty loam textural class and an average pH of 6.8. The total area of the experiment is 82.65 m2, it is 14.5 m long and 5.7 m wide, it has 16 experimental units and each unit has an area of 2.4 m, its measurements are 3 m long and 0.8 m wide. The distance between experimental units is 0.5 m. The study cultivars are Red Silk, Punta Blanca, Crimson Giant and Cherry Belle, for an adequate evaluation of the study factors, the following variables were taken into account: plant height ( cm), leaf length (cm), leaf width (cm), number of active leaves per plant, root weight (g), root diameter (cm) and agricultural yield (kg / ha). The SPSS Statistics version 25 program was used, with a reliability in the estimate of 95% (α = 0.05) for the evaluation of morphological and productive parameters of four radish cultivars in the canton arenillas, for which the analysis was used ANOVA variance of one factor in each of the variables (plant height, leaf length, leaf width, number of active leaves, root weight, root diameter and agricultural yield). In case the different cultivars presented statistical differences, a range test and multiple comparisons (Post-Hoc test) were applied to know between which cultivars there are differences or similarities. The cultivar that presents the greatest adaptability to these edaphoclimatic conditions is Crimson Giant, since it presents better results in most of the variables evaluated, with an average agricultural yield of 15,395.75 kg / ha, while the least recommended cultivar for this area is Punta Blanca due to its low yield of 12,947.75 kg / ha.
En Ecuador existen aproximadamente 14455 hectáreas cultivadas de rábano, las principales provincias productoras se encuentran al norte del país como Imbabura, Tungurahua, Cotopaxi y Chimborazo. El rábano es un alimento formado por gran cantidad de agua como elemento principal, así como hidratos de carbono y fibra, por lo que aporta niveles bajos de calorías, siendo recomendado por nutricionistas en dietas reguladoras de peso, contiene una importante cantidad de vitaminas, de las que se destacan las del grupo C y los folatos. Los del grupo C disponen de acción antioxidante, estos intervienen en la prevención de enfermedades como las cardiovasculares o degenerativas y favorecen la formación de colágeno, dientes, huesos o glóbulos rojos. El área del ensayo se encuentra ubicado en las siguientes coordenadas geográficas: longitud de 80°06’48.51” W; latitud 3°45’27.67” S, y una altura de 197 msnm. Se realizó en el sitio La Florida de la Parroquia Palmales del Cantón Arenillas. El área corresponde al clima tropical megatérmico seco a semihúmedo cuyas principales características corresponde a un total pluviométrico anual comprendido entre 1000 y 1500 mm, recogidos de diciembre a mayo, la estación seca es muy marcada, se extiende de junio a noviembre; y las temperaturas medias elevadas son superiores a 24°C de acuerdo al mapa de taxonomía de suelos del Atlas de la Provincia de El Oro. La clasificación taxonómica del suelo, clase textural franco limoso y un pH promedio de 6,8. El área total del experimento es de 82.65 m2, tiene un largo de 14.5 m y de ancho 5.7 m, cuenta con 16 unidades experimentales y cada unidad tiene un área de 2.4 m, sus medidas son de 3 m de largo y 0.8 m de ancho. La distancia entre unidades experimentales es de 0.5 m .Los cultivares de estudio son Red Silk, Punta Blanca, Crimson Giant y Cherry Belle, para una adecuada evaluación de los factores de estudio, se tomaron en cuenta las siguientes variables: altura de la planta (cm), longitud de la hoja (cm), ancho de la hoja (cm), número de hojas activas por planta, peso de raíz (g), diámetro de la raíz (cm) y rendimiento agrícola (kg/ha). Se utilizó el programa SPSS Statistics versión 25, con una confiabilidad en la estimación del 95% (α=0,05) para la evaluación de parámetros morfológicos y productivos de cuatro cultivares de rábano en el cantón arenillas, para lo cual se utilizó el análisis de varianza ANOVA de un factor en cada una de las variables (altura de la planta, longitud de la hoja, ancho de la hoja, numero de hojas activas, peso de la raíz, diámetro de la raíz y rendimiento agrícola). En caso de que presentaran diferencias estadísticas los diferentes cultivares, se aplicó prueba de rangos y comparaciones múltiples (prueba Post-Hoc) para conocer entre que cultivares hay diferencias o similitudes. El cultivar que presento mayor adaptabilidad a estas condiciones edafoclimáticas es Crimson Giant, ya que presenta mejores resultados en la mayoría de variables evaluadas, con un rendimiento agrícola promedio de 15395,75 kg/ha, mientras que en cultivar menos recomendado para esta zona es el Punta Blanca por su bajo rendimiento de 12947,75 kg/ha.
Keywords: RÁBANO; CULTIVAR; PARÁMETROS; RENDIMIENTO